1998
DOI: 10.1203/00006450-199812000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Stature, Growth, and Short-term Changes in Height and Weight in Normal Prepubertal Children

Abstract: Human growth is a nonlinear process with marked variation in growth rate during the short-term. It is not known how long-term height gain or stature is influenced by short-term changes in height and weight. This study has addressed these issues by using thrice weekly height and weight measurements during 1 year in 43 normal prepubertal children (aged 5.7-7.7 y) to construct individual height and weight velocity curves by regression analysis. The former were comprised of 3 to 6 growth spurts separated by stasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…A higher level of physical activity during spring than during winter may be a likely explanation for the changes in gains in body weight and body composition during winter and spring (22). Two newer studies are comparable with our study regarding latitude and population characteristics (11,12). Gelander et al found a peak in height velocity during spring among 50 Swedish 7-11-y olds measured in 1992-1993 (11); no data were available on weight or body composition.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A higher level of physical activity during spring than during winter may be a likely explanation for the changes in gains in body weight and body composition during winter and spring (22). Two newer studies are comparable with our study regarding latitude and population characteristics (11,12). Gelander et al found a peak in height velocity during spring among 50 Swedish 7-11-y olds measured in 1992-1993 (11); no data were available on weight or body composition.…”
Section: Discussionsupporting
confidence: 73%
“…Based on data from prepubertal British children, Tillmann et al concluded that in addition to a strong seasonal trend (height and body weight gains both highest during spring), linear growth was comprised of three to six yearly growth spurts separated by stasis, whereas weight gain was characterized by two to five periods of weight gain separated by periods of weight loss (12). Their study setup differed from ours by having fewer study subjects (n = 43), but more frequent measurements (biweekly for 1 y) and reporting average number, length and amplitude of height velocity peaks, and periods with growth stasis, weight gain, and weight loss based on averages of smooth estimates from individual height and weight velocity profiles (12). Most of the previous studies on seasonal variation in growth are not contemporary and results may reflect seasonal variations in food availability (1,9), impacts of infectious diseases (7), or other factors which are less relevant in contemporary cohort of school-aged children in highincome countries.…”
Section: Seasonality In Growth Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations may be relevant to previous conflicting reports regarding simultaneity versus. lag in the relationships between the timing of weight and height growth (37,38), suggesting effect modification by sex differences and accompanying environmental sensitivities. Males' reliance on fat stores for growth has been reported to be greater than females in late gestation (10), and phase shifts in weight and length growth have been reported to characterize the male fetus by contrast with copulsatility, more common among females (39).…”
Section: Discussionmentioning
confidence: 99%
“…who reported that in healthy prepubertal English children, growth starts to decrease in August, reaches a nadir in January, and exhibits a marked spurt from March to July (15,16). Since there are no major climatic and geographic differences between England and Germany (temperate climate, degree of latitude 58 8 249 8 and 55 8 247.5 8 respectively), the same subdivision was used even though it resulted in time intervals of different lengths (5 vs 7 months)…”
Section: Study Protocolmentioning
confidence: 99%